ANALYSIS OF AIR CARGO SECTOR CONTRIBUTION WITHIN THE AVIATION INDUSTRY TO NATIONAL LOGISTICS AND ECONOMIC RESILIENCE: ANALYSIS OF AIR CARGO SECTOR CONTRIBUTION WITHIN THE AVIATION INDUSTRY TO NATIONAL LOGISTICS AND ECONOMIC RESILIENCE - Achnihadian, Janjan; Dewi Puspaningtyas Feani (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study analyzes the air cargo sector's contribution to Indonesian logistics efficiency and economic resilience. Findings show air cargo is a strategic solution for high-value and time-sensitive goods, while playing a crucial role in connecting hard-to-reach archipelagic regions. The sector not only supports e-commerce and SMEs but also stands as a pillar of national resilience through economic diversification and mitigating supply chain disruptions during crises. Despite challenges like regulations and infrastructure, enabling factors such as the growth of e-commerce and sustainable investments, including through Green HRM, indicate the sector's great potential to strengthen Indonesia’s competitiveness and economic fortitude.